Pedagogical Conditions For The Formation Of Information Competence In Students On The Basis Of The Prevention Of Vertical Adhesion - Yozieva Umida Lutfullayevna (Genius Publishing Group, 2023)
This article discusses the special program developed for the formation of information competence among students of general secondary educational institutions based on the prevention of virtual addiction and the methodology of conducting extracurricular activities through this program.
Keywords: Information; threats; injury; safety